Morphological Electrical and Hardness Characterization of Carbon Nanotube-Reinforced Thermoplastic Polyurethane (TPU) Nanocomposite Plates (2023)
The impacts on the morphological, electrical and hardness properties of thermoplastic polyurethane (TPU) plates using multi-walled carbon nanotubes (MWCNTs) as reinforcing fillers have been investigated, using MWCNT loadings between 1 and 7 wt%. Plates of the TPU/MWCNT nanocomposites were fabricated by compression molding from extruded pellets. An X-ray diffraction analysis showed that the incorporation of MWCNTs into the TPU polymer matrix increases the ordered range of the soft and hard segments. SEM images revealed that the fabrication route used here helped to obtain TPU/MWCNT nanocomposites with a uniform dispersion of the nanotubes inside the TPU matrix and promoted the creation of a conductive network that favors the electronic conduction of the composite. The potential of the impedance spectroscopy technique has been used to determine that the TPU/MWCNT plates exhibited two conduction mechanisms, percolation and tunneling conduction of electrons, and their conductivity values increase as the MWCNT loading increases. Finally, although the fabrication route induced a hardness reduction with respect to the pure TPU, the addition of MWCNT increased the Shore A hardness behavior of the TPU plates